PENGARUH PERILAKU KONSUMEN TERHADAP BISNIS E-COMMERCE SHOPEE INDONESIA - Gabrielle Michaela K (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
This research aims to explore this further. With a focus on exploring the impact of consumer behavior on Shopee Indonesia's e-commerce business development, this research summarizes a detailed and systematic literature review. Through the use of the Systematic Literature Review (SLR) analysis method, this research seeks a holistic understanding of how consumer behavior can shape and influence business dynamics in a rapidly growing e-commerce platform. The data used in this research was obtained through various relevant sources available on the internet, ensuring a diversity of perspectives in the analysis. The research results obtained reveal that consumer behavior has a very significant role in shaping the success of e-commerce businesses, particularly in the context of e-commerce application Shopee Indonesia. The findings provide a deep understanding of how important it is for companies to continuously adapt to the dynamics of consumer behavior. This is not only as an effective business strategy, but also as a key to ensuring business continuity and long-term growth. Therefore, understanding and responding to changes in consumer behavior is a must for companies, in an effort to optimize business performance and maintain competitiveness in an increasingly competitive market. Thus, this research not only makes a theoretical contribution to the understanding of consumer behavior in the context of e-commerce, but also has strong practical implications for business managers and other stakeholders in designing effective and sustainable business strategies.